α-Lipoic acid mitigates age-related macular degeneration via ferroptosis: integrative multi-omics and network pharmacology - Zhang, Yaqiong; Chen, Yuanyuan; Sun, Chenglin; Li, Fang; Shen, Yin (Frontiers in Pharmacology, 2025)
BackgroundAge-related macular degeneration (AMD) is a leading cause of irreversible vision loss among the elderly. α-Lipoic acid (ALA), a naturally occurring antioxidant and iron-chelator, has shown potential in modulating ferroptosis, but its mechanism in AMD remains unclear.MethodsNetwork pharmacology, transcriptomic profiling, and machine learning were used to identify potential molecular targets of ALA in AMD. Core genes were identified through interaction network construction, functional enrichment analysis, and machine learning-based screening. Molecular docking and molecular dynamics simulations were performed to assess the binding affinity and stability between ALA and its predicted targets. In vivo validation was conducted using a sodium iodate (SI)-induced AMD mouse model, with retinal structure, function, oxidative stress, and gene expression evaluated through behavioral tests, histological staining, and qRT-PCR.ResultsWe identified six ferroptosis-related core targets (AHCY, DHODH, MAPK1, MAPK8, NOS2, and HMOX1) of ALA implicated in AMD. Molecular docking revealed strong binding affinities between ALA and these six targets, with dynamic simulations confirming stable interactions, particularly with HMOX1 and MAPK1. In the SI-induced AMD mouse model, ALA significantly preserved retinal structure, maintained visual function, and reduced oxidative stress and iron accumulation. qRT-PCR confirmed that ALA exerted differential effects on the expression of the six genes, demonstrating a context-dependent regulatory mechanism.ConclusionThis study provides multi-level evidence that ALA protects against AMD by modulating ferroptosis-related pathways and restoring retinal structural integrity and functions. These findings warrant further investigation into the therapeutic potential of ALA in AMD.